Estudo comparativo do desempenho de membranas de látex natural extraído da hevea brasiliensis em diferentes preparos no reparo de defeitos ósseos - Moura, Jonas Marçal Lázaro de (2012)
Natural rubber membranes made of latex extracted from Hevea brasiliensis are capable to stimulate angiogenesis and accelerates the repair process. The latex is usually preserved in alkaline medium, consisting of ammonia solution, and one question that remains concerns the effect of this substance in the behavior of this biomaterial. Therefore, the objective of this comparative study was to assess the performance of membranes made of natural latex prepared with three different methods: polymerized immediately after collection without the use of ammonia (L1); polymerized after preservation in ammonia solution (L2); and polymerized after storage in ammonia, followed by Soxhlet technique for the extensive extraction of substances (L3). Polytetrafluoroethylene (PTFE) membrane, the gold standard in Guided tissue regeneration procedures was used as control. Thirty adult male New Zealand rabbits were used in the study. Two 10 mm diameter bone defects were surgically made in the calvaria of the animals. Defects were treated with GBR using L1, L2, L3 or PTFE membranes (n=15 for each membrane). Ten animals at a time were euthanized after 7, 20 and 60 days postoperatively. For each kind of membrane, a total of 5 histological samples were obtained, and bone regeneration results were assessed microscopically. Samples collected at 7 and 20 days after surgery presented no significant differences among treatments. After 60 days, defects covered with L1 membranes showed a significantly larger bone formation area, evaluated by histomorphometry, in comparison to the other groups (P<0.05, ANOVA, Tukey). In addition, bone tissue hypersensibilization for L1 and PTFE membranes was also investigated, in 6 additional rabbits with no differences being found, in the microscopic analysis, between samples collected from sensibilized and non-sensibilized animals. It can be concluded that: i) the natural rubber latex membranes were effective as a biological barrier ii) membranes prepared without ammonia presented better results to other membranes and the control iii) the latex membrane without ammonia is biocompatible, and do not caused sensitization of the bone tissue